Predominance of six different hexanucleotide recoding signals 3′ of read-through stop codons - Harrell, Lance (Oxford University Press, 2002)
Redefinition of UAG, UAA and UGA to specify a standard amino acid occurs in response to recoding signals present in a minority of mRNAs. This ‘read-through’ is in competition with termination and is utilized for gene expression. One of the recoding signals known to stimulate read-through is a hexanucleotide sequence of the form CARYYA 3′ adjacent to the stop codon. The present work finds that of the 91 unique viral sequences annotated as read-through, 90% had one of six of the 64 possible codons immediately 3′ of the read-through stop codon. The relative efficiency of these read-through contexts in mammalian tissue culture cells has been determined using a dual luciferase fusion reporter. The relative importance of the identity of several individual nucleotides in the different hexanucleotides is complex.